Sustainable development perspectives in Nordic physical education curricula : a cross-country comparison of the status and pre-conditions - Lundvall, Suzanne; Gisladottir, Thordis; Lauritzen, Åge; Munk Svendsen, Annemari; Salin, Kasper; Stefansdottir, Runa; Fröberg, Andreas (Routledge, 2024)
In the present study, we present a cross-country comparison of the status and condition of sustainable development (SD) in the Nordic physical education (PE) curricula. The aim of the study was to increase knowledge of how SD perspectives are represented and conceptualised in the Nordic PE curricula. An expert-driven research approach was used where representatives from Denmark, Finland, Iceland, Norway, and Sweden provided country overviews and completed surveys to elaborate on the status, pre-conditions, prospect/future, and research initiatives in relation to SD in PE. The study shows that SD perspectives seldom are explicitly mentioned in the Nordic PE curricula, and that little is known regarding how PE teachers understand SD in relation to PE goals and content in their countries. Suggestions on specific SD goals to focus on in Nordic PE, as well as suggestions on future research are provided and discussed in the paper. peerReviewed